A New Printed Antenna Structure Design for Medical Applications (2.4 GHz) by Adding Metamaterial Structures under the Antenna Patch - سعيدي أمجد; صالح السموءل; علي صادق (Latakia University Journal -Engineering Sciences Series, 2022)
This paper presents a new design for a printed antenna operating at a frequency of (2.4 GHz) suitable for wireless communication equipment used in medical applications for telehealth, which requires providing the best quality of information transfer between the patient’s device and the health monitoring center device.In the first stage we designed a reference azeotropic antenna operating at the frequency of 2.4 GHz. Then we took advantage of the electromagnetic properties resulting from the interaction of the electromagnetic field with the metamaterials structures (Mms) or the so-called negative structures of electrical permittivity and magnetic permeability (negative index refraction structure) in order to improve the efficiency of the proposed antenna by adding a metamaterial structure which operates at the 2.4 GHz frequency under the antenna patch. The proposed antenna was designed and analyzed by using the HFSS (High Frequency Structure Simulation), which is a virtual laboratory that enables us to analyze the antenna parameters (frequency, reflection coefficient, radiation pattern, gain) and allows a large number of tests to be performed until the appropriate design is reached. The Matlab program was also used to compare the antenna efficiency before and after adding the metamaterial structure, and to obtain the proposed metamaterial structure coefficients (electrical permittivity, magnetic permeability, index refraction).